ENHANCING STUDENTS’ SPEAKING ABILITY: THE ROLE OF THE CUBING TECHNIQUE - Musrifah, Musrifah; Rahmawati, Istiqomah Nur; Meisuri, Meisuri (Journal of Linguistics and Social Sciences, 2023)
This study addresses the issue of students dealing with verbal expressiveness and speaking difficulty. It looks examines how the Cubing Technique affects the speaking abilities of eleventh-grade students in a senior high school. A total of 69 students from various classes were divided into two groups: experimental and control. The experimental group was taught the Cubing Technique, while the control group was taught by the technique that is usually used by the teacher, the Mind Mapping Technique. Pre- and post-tests used a quantitative research method and a quasi-experimental design to assess five criteria: pronunciation, grammar, vocabulary, fluency, and comprehension. The Cubing Technique had a substantial influence (Sig. 2-tailed = 0.001) on students' speaking abilities in the first semester of eleventh grade, according to an independent t-test done in SPSS 16. This study adds to our understanding of effective language teaching approaches, specifically the positive impact of the Cubing Technique in a senior high school in Purbolinggo in the 2023/2024 academic year.